Brittany Price: capstone - Price, Brittany, artist (Colorado State University. Libraries, 2016)
The artist's statement: It's funny; we pay so little attention to the objects that we interact with on a daily basis. And yet our cars, our clothes, even our coffee cups, were thoughtfully created by designers looking to make the world a bit more eye-catching. Our world can become so monotonous that we forget to enjoy the little things in life. But if you pay attention, you can see how visual art is intertwined with almost every aspect of our lives. I became a graphic artist because I was fascinated by the symbiotic relationship between art and society and the power it had to affect people. I want be the reason someone smiles when they get a cute card, to make someone laugh when they read a funny comic, and to enlighten someone to an important issue when they see an info poster. To me, being able to influence someone's perception of the world with art is the greatest superpower of all. And I plan to use that superpower to help others by creating visually captivating pieces that draw attention to important programs, ideas, businesses, etc. that are making our world a better place. As an artist, I enjoy playing with all types of design, but I primarily focus on digital illustration via vector graphics, as they are easy to manipulate and rescale. When I first entered the design world, my biggest struggle was digital illustration. I think my desire to become better at illustration drove me to select project ideas that revolved around practicing this skill until I was able to quickly and effectively create any image I wanted. My favorite types of design are character design, digital illustration, and branding as apparent in the pieces I have provided for my BFA submission. I enjoy exploring the boundaries between reality and fantasy and like the challenge of trying to place an alternate world within the context of a real business situation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design